Our Ancient Forests: Virtual Visiting and Art for Conservation - Morgan-Thorp, Emma (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2021)
This article reflects upon two virtual reality experiences included in the Our Ancient Forests exhibition at the Sunshine Coast Arts Council: Sanctuary: The Dakota Bear Ancient Forest Experience and Tree Earth Sky. It works through questions about the use of virtual reality both as a means of visiting a wild place and as a means of moving audiences to environmentalist and anticolonial action. In doing so, it considers settler desires for deeper relationships with wild places and the more-than-human world and settler responsibilities within environmental and anticolonial movements.